Harmonization of Blockchain-Based Electronic Land Certificate Regulations from the Perspective of Information Disclosure and Personal Data Protection - Lily Kalyana (Siber Nusantara Research, 2026)
The digital transformation of land administration through the implementation of electronic certificates opens up opportunities for increased efficiency, transparency, and legal certainty in the land registration system in Indonesia. Blockchain technology offers advantages in the form of data integrity, transaction transparency, and decentralized verification mechanisms, but these characteristics also pose legal challenges, particularly regarding the protection of personal data of land rights holders. This study aims to analyze the normative conflict between the principle of public information transparency and the state's obligation to protect personal data in the blockchain-based land registration ecosystem, while simultaneously formulating an ideal regulatory harmonization model. The research method employed is normative juridical with a legislative, conceptual, and comparative approach through an analysis of the national legal framework, including the Basic Agrarian Law (UUPA), Government Regulation Number 24 of 1997 concerning Land Registration, Law Number 14 of 2008 concerning Public Information Disclosure, Law Number 11 of 2008 in conjunction with Law Number 19 of 2016 concerning Electronic Information and Transactions, and Law Number 27 of 2022 concerning Personal Data Protection, as well as comparisons with international practices such as Estonia and the GDPR approach in the European Union. The study reveals a tension between the immutable and distributed nature of blockchain transparency and personal data protection principles such as consent, data minimization, and the right to correction. Existing regulations still do not fully accommodate decentralized technology designs, potentially creating legal loopholes. The proposed harmonization model emphasizes the use of permissioned blockchains, layered access systems, privacy-by-design, and the separation of sensitive data storage through off-chain mechanisms. A techno-legal approach is crucial to ensure that technological innovation aligns with the protection of citizens' constitutional rights and the principle of legal certainty in digital land administration.